The Biogeography of Forest Soil Microbial Functional Diversity Responds to Forest Types across Guangxi, Southwest China - Wanxia Peng (MDPI AG, 2021)
Vegetation and soil have spatial distributions at different scales, while the spatial distribution of soil microorganisms and factors driving their distribution are still unclear. We aimed to reveal the spatial pattern of microbial functional diversity and to identify its drivers in forest soils at a regional scale. Here, we performed an investigation of microbes across several forest types covering an area of 236,700 km2 in Guangxi, southwest China. We examined a total of 185 samples for soil microbial functional diversity using Biolog EcoPlates. The soil microbial functional diversity had strong spatial heterogeneity across the Guangxi region. The distribution of microorganisms in forest soils was mainly determined by total nitrogen, available N, and C:N ratio, and stand age. We found that coniferous forests, especially pine forest, exhibited lower functional diversity, but the reverse was true for deciduous broadleaf forest/mixed evergreen and deciduous broadleaf forest. Our findings suggested that a heterogeneous distribution of microbial functional diversity in forest soils is related to forest types in Guangxi, China. In conclusion, high soil microbial functional diversity is favored in subtropical forests with looser soil structure, lower soil C:N ratio, greater total soil nitrogen and available nitrogen concentration, and broad-leaved tree species.